The ghost town mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (Morton Grove, Ill. : A. Whitman, 1999)
While visiting a recent purchase of Grandfather's, a ghost town in the Rocky Mountains, the Aldens encounter a mystery involving a run-down motel and a woman who may be a ghost.
Keywords: Ghost towns -- Fiction; Ghosts -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories; Rocky Mountains -- Fiction